Defund the Police: Moving Towards an Anti-Carceral Social Work - Jacobs, Leah A.; Kim, Mimi E.; Whitfield, Darren L.; Gartner, Rachel E.; Panichelli, Meg; Kattari, Shanna K.; Downey, Margaret Mary; McQueen, Shanté Stuart; Mountz, Sarah E. (Journal of progressive human services, 2021)
This article addresses social work's place in the movement to "defund the police." We argue that social work's collaboration with police and use of policing constitutes carceral social work. In defining carceral social work, we specify the ways in which coercive and punitive practices are used to manage Black, Indigenous, other people of color, and poor communities across four social work arenas - gender-based violence, child welfare, schools, and health and mental health. To inform anti-carceral social work, we provide examples of interventions in these arenas that dismantle police collaborations and point to life-affirming, community-centered, and mutual aid alternatives.